Numerical investigation on noise and flow characteristics of a circular cylinder with helical grooves - Tao Li; Ningzhou Lu (Discover Applied Sciences)
Abstract The paper presents a numerical investigation on the use of helical groove to reduce flow-induced noise from a circular cylinder. The study primarily explores the effects of groove pitch, groove depth ratio and groove profile on aerodynamic noise over a Reynolds number range of 2.8 × 104 to 8.6 × 104. Currently, there are limited studies focusing on the influence of helical grooves on the flow-induced noise around circular cylinders. Acoustic results reveal that at a Reynolds number of 4.1 × 104, when the groove pitch is 400 mm, the groove depth ratio is 0.01, and the groove profile is circular, the maximum sound pressure level (SPL) at the far-field monitoring point is reduced by up to 18 dB compared to the baseline model. However, as the pitch decreases from 400 to 100 mm, the noise reduction effect diminishes. Increasing the groove depth ratio from 0.01 to 0.03 results in only a 4.7 dB reduction in peak SPL compared to the baseline. The groove profile also plays a critical role, with circular grooves showing superior noise reduction performance compared to triangular ones. The sound directivity of the cylinders exhibits symmetry. For the cylinder with circular grooves (400 mm pitch, size ratio of 0.01), the OASPL is higher than that of the baseline model in the angular range of 0–45°, and lower in the range of 45–90°. Flow simulation results indicate that the observed noise reduction in the far field is primarily attributed to weakened vortex shedding in the wake region. The study concludes that selecting appropriate groove pitch, depth ratio, and profile can effectively mitigate noise generated by bluff body flows. These findings offer valuable insights for noise control in various engineering applications.